In situ detection of microplastics: single microparticle-electrode impacts - Shimizu, K; Sokolov, S; Kätelhön, E; Holter, J; Young, N; Compton, R (Wiley, 2017)
Particle-impact electrochemistry is employed to study spherical polyethylene microparticles suspended in an aqueous solution. This electrochemical method detects polyethylene microparticles impacting on a carbon fiber electrode generating a transient current response or "spike". We interpret the physio-chemical origin of the spikes and accurately identify particle size distributions and concentrations for microparticles of sizes 1-10μm.